Surviving Modernity Through Magic: A Participatory Study on Pekalongan Sintren Performance - Ratna Asmarani (MOZAIK HUMANIORA, 2019)
This study aims to analyze how magic is performed in Sintren and what survival strategies are applied by its performers in the modern era. Sintren is a unique folk art of Pekalongan performed by a regional arts group called Kudo Bekso Utomo from Pringsurat village, Kajen sub-district, Pekalongan on June 23rd, 2018 during the Syawalan festivals in Linggo Asri village, Pekalongan, Central Java, Indonesia. To achieve this goal, the researcher uses qualitative method. Data are collected by participatory observation and interview with the Sintren dancers, the Sintren shamans, and the Sintren audiences. Furthermore, the data are analyzed by the concept of performance by Goffman together with the concept of “magic” and “trick” by O’Connor. This study finds that Sintren folk art is a unique performance which is not a trick, but full of magic. Besides, this study also reveals that Kudo Bekso Utomo survives to maintain this traditional performance by applying economic strategies, such as using simpler costumes/performance tools, always conducting performance in every event whether formally invited or not, as well as trying to present non-virgin dancer. These strategies even can be adopted or adapted by other regional arts groups to cope modernity